1999
DOI: 10.1142/s0218348x99000311
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Transition: Hierarchical Structure and Noise Effect

Abstract: A Sierpinski gasket with continuous trajectories is presented as an example of the fractal transition that characterizes the behavior of dissipative dynamical systems excited by external temporal inputs. Using this example, we investigate the fractal transition from two points of views, i.e. a hierarchical structure and a noise effect. Depending on internal and external parameters, the structure can be geometrically classified as one of three types, i.e. totally disconnected, just-touching, and overlapping. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…In addition, as the results of the inverse proportional relationship D ∝ 1/T in this study are almost in agreement with the theoretical analysis reported in [Gohara & Okuyama, 1999b;, it is considered that the correlation dimension D 2 is inversely proportional to the switching-time length T . However, the following findings emerged when we analyzed the relationship.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In addition, as the results of the inverse proportional relationship D ∝ 1/T in this study are almost in agreement with the theoretical analysis reported in [Gohara & Okuyama, 1999b;, it is considered that the correlation dimension D 2 is inversely proportional to the switching-time length T . However, the following findings emerged when we analyzed the relationship.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we confirmed the inverse proportional relationship between T and the fractal-like feature D 2 in human pointing movement [Hirakawa et al, 2016]. Our purpose was to develop these studies on continuous tracking movements and to examine the regular relationship between T and D 2 , which is estimated by the transition state and which occurs when a human switches several attractors stochastically, based on a theoretical model [Gohara & Okuyama, 1999b;. It is assumed that an attractor underlies a movement pattern in a nonautonomous dynamical system with an external input [Gohara & Okuyama, 1999a].…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations